Energy Density Determination for L-PBFP of Ti-6Al-4V Alloy for Various Beam Diameters and Hatch Distances (Journal of Additive Manufacturing Technologies, 2022)
It is important to determine the appropriate energy densities to achieve an ideal (defect-free) production in the laser powder bed fusion process. In this study, energy density levels for Ti-6Al-4V alloy were determined through simulations with a model using a dynamic volumetric heat source. Undesirable situations such as fusion problems, balling, excessive evaporation, and keyhole regime are accepted as criteria for the evaluation. The developed process window covers analysis for different beam diameters of 50, 80, and 100 micrometers, and hatch distances ranging from 30 to 100 micrometers. Laser power and laser scan speed range from 50 to 200 W and 250 to 1500 mm/s, respectively. The results have shown that higher laser power with low scan speed causes high evaporation and keyhole formation.  On the other hand, unstable melt-pools, fusion problems and balling may be encountered for lower laser power with high scan speed. Consequently, the analysis results are to be used as a guide before further experimental tests.
Keywords: Laser powder bed fusion process; Additive manufacturing; Process window